Model and Data Engineering 5th International Conference, MEDI 2015, Rhodes, Greece, September 26-28, 2015, Proceedings - Bellatreche, Ladjel; Manolopoulos, Yannis (Programming and Software Engineering, 2015)
This book constitutes the refereed proceedings of the 5th International Conference on Model and Data Engineering, MEDI 2015, held in Rhodes, Greece, in September 2015. The 18 full papers and 9 short papers presented together with 2 invited talks were carefully reviewed and selected from 55 submissions. The papers are organized in topical sections such as modeling and meta modeling; ontology-based modeling, reasoning and reuse; event-B and modeling languages; context modeling and model transformation; data mining; query processing; modeling activities and inference; prediction and recommendation; requirement and systems engineering.